Examining the Socio-Economic Factors Affecting the Choice of Insurance Products in Nigeria - O. A. Ehiorobo; S. Okon; J.N Mojekwu (Unilag Journal of Humanities, 2019)
This study examined the socio-economic factors affecting the choice of insuranceproducts in Nigeria. Using the cross-sectional survey design and the conveniencesampling technique, a structured questionnaire was administered to 400 participants thathad contracted insurance policies in Lagos State, out of which 317 were deemed usablefor the study. An analysis was done using the t-test, and from the hypothesis tested, theresult revealed that family influence, religion, and income level influenced the choice ofinsurance policy in Nigeria. Based on the findings, it is recommended that the federalgovernment should continue sensitizing the public on the need for insurance and enactpolicies that will encourage low-income earners to participate in the purchase ofavailable insurance policies. Insurance companies on their own part should put in placepolicies which allow for prompt payment of claims, making sure their policies are explicitenough and they have employees with the right attitude.